Facile synthesis of composite tin oxide nanostructures for high-performance planar perovskite solar cells. (June 2019) - Singh, Mriganka; Ng, Annie; Ren, Zhiwei; Hu, Hanlin; Lin, Hong-Cheu; Chu, Chih-Wei; Li, Gang
Abstract: Metal oxide carrier transporting layers have been investigated widely in organic/inorganic lead halide perovskite solar cells (PSCs). Tin oxide (SnO2 ) is a promising alternative to the titanium dioxide commonly used in the electron transporting layer (ETL), due to its tunable carrier concentration, high electron mobility, amenability to low-temperature annealing processing, and large energy bandgap. In this study, a facile method was developed for the preparation of a room-temperature-processed SnO2 electron transporting material that provided a high-quality ETL, leading to PSCs displaying high power conversion efficiency (PCE) and stability. A novel physical ball milling method was first employed to prepare chemically pure ground SnO2 nanoparticles (G-SnO2 ), and a sol–gel process was used to prepare a compact SnO2 (C-SnO2 ) layer. The effects of various types of ETLs (C-SnO2, G-SnO2, composite G-SnO2 /C-SnO2 ) on the performance of the PSCs are investigated. The composite SnO2 nanostructure formed a robust ETL having efficient carrier transport properties; accordingly, carrier recombination between the ETL and mixed perovskite was inhibited. PSCs incorporating C-SnO2, G-SnO2, and G-SnO2 /C-SnO2 as ETLs provided PCEs of 16.46, 17.92, and 21.09%, respectively. In addition to their high efficiency, the devices featuring the composite SnO2 (G-SnO2 /C-SnO2 ) nanostructures possessed excellent long-term stability—they maintained 89% (with encapsulation) and 83% (without encapsulation) of their initial PCEs after 105 days (>2500 h) and 60 days (>1400 h), respectively, when stored under dry ambient air (20 ± 5 RH %). Graphical abstract: A facile new solid-state synthesis of composite Tin-oxide electron transport layer (ETL) leads to power conversion efficiency up to 21.09% for mixed-cation lead mixed-halide perovskite solar cells.Image 1 Highlights: A facile new solid-state synthesis of composite Tin-oxide electron transport layer (ETL) for efficient mixed-cation lead mixed-halide perovskite solar cells. A novel physical approach—using high-energy ball-milling method introduced to prepare high-quality ground SnO2 nanoparticle. The champion power conversion efficiency (PCE) of composite tin oxide nanostructures ETLs reached up to 21.09% and voltage as high as 1.22 V with weaker hysteresis (H = 0.01). The champion device featuring the composite tin oxide based ETL stable up to 105 days when stored under ambient air (20 ± 5 RH %).